1981
DOI: 10.1111/j.1528-1157.1981.tb04128.x
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Somatosensory Evoked Potential (ESEP): An EEG Sign Forecasting the Possible Occurrence of Seizures in Children

Abstract: In a population of 15,000 children, it was found that tactile stimulation, mainly tapping o n the soles or heels of the feet, could elicit high-voltage evoked potentials in the EEGs of 1% of them. A longitudinal study of 16 of these patients showed a stereotyped electroclinical evolution. At first, only extreme somatosensory evoked potential (ESEPs) were observed in nonepileptic children with normal EEG records first period). Then, after a variable delay, spontaneous EEG abnormalities appeared, first only duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
12

Year Published

1988
1988
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 9 publications
1
35
0
12
Order By: Relevance
“…We also wished to determine if tactileenhanced discharges are an EEG sign forecasting the possible occurrence of seizures in children, as hypothesised by De Marco and Tassinari (4). In this study, no patients were found to have developed epilepsy characterized by the stereotypic electroclinical pattern, as described by …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also wished to determine if tactileenhanced discharges are an EEG sign forecasting the possible occurrence of seizures in children, as hypothesised by De Marco and Tassinari (4). In this study, no patients were found to have developed epilepsy characterized by the stereotypic electroclinical pattern, as described by …”
Section: Discussionmentioning
confidence: 99%
“…In 1981, De Marco and Tassinari (4) found that in 1% of children without overt neurologic pathology, they could elicit high-voltage evoked potentials in the parietal and parasagittal region with tapping on the soles or heels of the feet. A longitudinal study of these patients showed a stereotypical electroclinical evolution occurring over 4 time periods.…”
mentioning
confidence: 99%
“…As porções distais dos membros inferiores (calcanhar ou artelhos) ou membros superiores (dedos ou região dorsal da mão) parecem ser os locais mais apropriados para a estimulação e obtenção de PE.A cada estímulo corresponde uma ponta bifásica ou polifásica, por vezes seguida de onda lenta. PE foram registradas em 1 a 3% das crianças examinadas em serviços de eletrencefalografia [2][3][4] . As PE decorrem de hiperexcitabilidade cortical, que também seria responsável pelo aparecimento de pontas espontâneas no EEG e poderia originar crises epilépticas.…”
Section: Somatosensory Evoked Potential In Children With Evoked Spikeunclassified
“…Nestas epilepsias a evolução é favorável e não há lesão cerebral. Podem ocorrer PE, também, em epilepsias generalizadas idiopáticas ou criptogênicas e parciais sintomáticas [3][4][5][6][7][8] . O potencial evocado somato-sensitivo (PES) tem sido estudado desde 1950 em pacientes adultos com patologias neurológicas mas só nos últimos anos passou a ser valorizado como rotina diagnostica em neurologia infantil [9][10][11][12] .…”
unclassified
“…Podemos observar que na faixa etária de 2 a 7 anos as PE apareceram em 7,26% das crianças com CF. A localização das PE foi parietal (P , P ou P ) em 12 dos 13 casos, Marco 3,5,7,8,9,21^ pesquisando sistematicamente pela percussão e estímulos táteis principalmente dos pés, obteve PE em cerca de 1% dos casos. Grande parte das crianças com PE buscaram atendimento por distúrbios de comportamento e/ou escolaridade e parte por CF e crises não febris repetidas, mas sem natureza reflexa.…”
Section: Materials E Métodounclassified